Asymmetric Synthesis of Spiro β‐Lactams via a Squaramide‐ Catalyzed Sulfa‐Michael Addition/Desymmetrization Protocol. Issue 20 (31st August 2016) - Chauhan, Pankaj; Mahajan, Suruchi; Kaya, Uğur; Valkonen, Arto; Rissanen, Kari; Enders, Dieter
Abstract: An efficient asymmetric synthesis of spirocyclohexenone β‐lactams bearing three contiguous stereocenters has been achieved in moderate to good yields and high stereoselectivities. The protocol involves the combination of a squaramide‐catalyzed sulfa‐Michael addition under desymmetrization via a dynamic kinetic resolution of racemic 2, 5‐cyclohexadienones. Abstract :